1993
DOI: 10.1103/physrevd.48.816
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous symmetry breaking of (1+1)-dimensionalφ4theory in light-front field theory

Abstract: We study spontaneous symmetry breaking in (l+l)-dimensional qh4 theory using the light-front formulation of field theory. Since the physical vacuum is always the same as the perturbative vacuum in light-front field theory the fields must develop a vacuum expectation value through the zero-mode components of the field. We solve the nonlinear operator equation for the zero mode in the one-mode approximation. We find that spontaneous symmetry breaking occurs at Xcritical = 47r (3 + 4 p 2 , which is consistent wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 11 publications
(13 reference statements)
6
94
0
Order By: Relevance
“…The solution of the DLCQ constraint equation for the zero mode can be used to study the critical coupling and critical exponents [71]. The solution can also be used to develop a controlled series of effective interactions that improve the numerical convergence [75].…”
Section: φ 4 2 Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…The solution of the DLCQ constraint equation for the zero mode can be used to study the critical coupling and critical exponents [71]. The solution can also be used to develop a controlled series of effective interactions that improve the numerical convergence [75].…”
Section: φ 4 2 Theorymentioning
confidence: 99%
“…These effective interactions are typically due to end-point corrections where, although the wave function goes to zero as x i goes to zero, it does so slowly enough that the integral has a nonzero contribution which is missed by DLCQ's neglect of the x i = 0 points in its trapezoidal approximation. They can be computed by solving the constraint equation, either nonperturbatively [71] or as an expansion in powers of 1/K [75]. There can also be quantum corrections to the constraint equation, such as contributions from zero-mode loops [76,77].…”
Section: Discretized Light-cone Quantizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of model field theories have shown that certain aspects of vacuum physics can in fact be reproduced by a careful treatment of the field zero modes. For example, solutions of the zero mode constraint equation in φ 4 1+1 [3] exhibit spontaneous symmetry breaking [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%